Subsequent Carcass Merit of Feedlot Cattle May Be Improved by Limit Feeding a High-Energy Diet During the Backgrounding Phase - M. A. Scilacci; M. A. Johnson; C. E. Hissong; S. P. Montgomery; T. G. O'Quinn; A. J. Tarpoff; E. C. Titgemeyer; K. Montgomery; G. T. Tonsor; C. I. Vahl; D. U. Thomson; W. R. Hollenbeck; et al. (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:Determine and analyze the impact of limit feeding a high-energy diet in the backgrounding phase, primarily based on dry-rolled corn and Sweet Bran (Cargill Animal Nutrition, Blair, NE), on animal performance in the finishing phase and carcass merit. Study Description:This project was a continuation of the performance backgrounding study previously conducted at the Kansas State University Beef Stocker Unit. All cattle were shipped to Pratt Feeders (Pratt, KS) on August 26–27, 2019, and were fed in four separate feed groups (approximately 100 head/pen) according to standard operating practices at the feed yard. Original backgrounding treatment integrity was maintained. Cattle were processed at National Beef (Dodge City, KS) on January 14 and February 4, 2020, and carcass data were obtained. The Bottom Line:Limit feeding a high-energy diet to cattle in the backgrounding phase appears to improve muscle deposition, especially in the light-sort cattle during the finishing phase.
Keywords: limit feeding; carcass merit; liver abscesses